2020
DOI: 10.1002/nau.24326
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerance of botulinum toxin injections after sacral nerve stimulation failure for idiopathic overactive bladder

Abstract: Introduction Management of idiopathic overactive bladder (iOAB) after the failure of sacral nerve modulation (SNM) is very challenging. To the best of our knowledge, no study has evaluated the use of botulinum toxin A (BoNT‐A) after SNM failure for iOAB. The aim of this study is to evaluate the tolerance and efficacy of BoNT‐A injection after the failure of SNM for iOAB. Methods We conducted a retrospective multicentric analysis of all patients who had received either onabotulinumtoxinA or abobotulinumtoxinA i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 27 publications
1
10
0
1
Order By: Relevance
“…The difference in the location of action between BoNT‐A and SNM also suggests that previous treatment with BoNT‐A, should not affect the success rate of subsequent treatment with SNM, and vice versa. In literature, the recent study by Baron et al 17 confirms BoNT‐A can be used in SNM non‐responders, although a higher BoNT‐A discontinuation rate was reported at long‐term follow‐up. Trinh et al 18 also concludes BoNT‐A after failed SNM remains an option but showed lower success rate compared to patients without prior SNM.…”
Section: Discussionmentioning
confidence: 99%
“…The difference in the location of action between BoNT‐A and SNM also suggests that previous treatment with BoNT‐A, should not affect the success rate of subsequent treatment with SNM, and vice versa. In literature, the recent study by Baron et al 17 confirms BoNT‐A can be used in SNM non‐responders, although a higher BoNT‐A discontinuation rate was reported at long‐term follow‐up. Trinh et al 18 also concludes BoNT‐A after failed SNM remains an option but showed lower success rate compared to patients without prior SNM.…”
Section: Discussionmentioning
confidence: 99%
“…Kirkpatrick et al [20] performed a retrospective analysis and found that when patients with urge incontinence OAB received BTX therapy after failure of SNM therapy, it was even more effective than was BTX therapy. By contrast, recent studies reported that the success rate when OAB patients chose BTX therapy after the initial choice and ineffectiveness of SNM therapy was only 27%-39% [21,22]. Currently, there is a need for more high-quality research before one can confirm the efficacy of OAB in those who receive BTX therapy after the failure of initially undergoing SNM therapy.…”
Section: Discussionmentioning
confidence: 98%
“…Likewise, further recommendations on treatments after the failure of SNM or BTX are lacking. We acknowledge this is a missed opportunity since literature on this topic is scarce 19,20 . On other topics, such as the choice between AC and β3A, the maximum number of drugs that should be tried in monotherapy before proceeding to combination therapy, and the role of PTNS, there was also no consensus.…”
Section: Discussionmentioning
confidence: 99%